Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic - Barroso, Rômulo; de Paiva, Paulo Cesar; Nogueira, João Miguel De Matos; Fukuda, Marcelo Veronesi (Zootaxa, 2017)
We describe herein ten species of Syllidae from the Southern Brazil continental slope (700–2000 m deep), belonging to the genera Anguillosyllis, Exogone, Parexogone, Prosphaerosyllis, Sphaerosyllis and Syllis. Out of those, three species are new to science and six are formally reported for Brazil for the first time. Some synonymies are proposed and a taxonomic key for all described species of the genus Anguillosyllis is provided.